Using Myofunctional Devices in the Complex Treatment of Orthodontic Patients: Implementation in the Healthcare Policy System - Makhlynets , Nataliia; Kokoshko, Myroslava; Pyuryk, Markiyan; Plishka , Dana; Kotyk , Taras (Actual Dentistry, 2025)
Objective. To determine dentoalveolar and skeletal effects produced in mature patients with low tongue posture by the Carriere Motion Class III (CM3) appliance, followed by fixed appliances and myofunctional therapy by Froggy Mouth Appliance (FMA). To justify the need for regulatory implementation of these technologies in clinical practice as part of public health policy, and to establish the legal framework supporting an interdisciplinary approach in orthodontic care. Methods. This clinical study involved 15 patients diagnosed with mandibular prognathism (Class III malocclusion), aged between 18 and 21 years, divided into two groups. Patients in Group 1 received conventional treatment using fixed orthodontic appliances (Carriere Motion system and bracket system). In Group 2, treatment was supplemented with the Froggy Mouth myofunctional appliance to correct tongue posture. All patients underwent clinical and laboratory assessments. Results and Discussion: all participants demonstrated high levels of anxiety, with scores exceeding 45 on the Spielberger State-Trait Anxiety Inventory. Furthermore, 86.7% reported experiencing chronic stress (87.5% in Group 1 and 85.7% in Group 2). Most patients associated stress with social factors, minimal social interaction, and the expansion of online learning formats (88.3% in both groups). The average treatment duration in Group 1 was approximately 18 months, compared to 14 months in Group 2. Following the completion of the study, patients in Group 2 were additionally prescribed FMA to normalize tongue posture and prevent relapse. Scientific Novelty. The findings of clinical and cephalometric examinations of patients in Groups 1 and 2 confirm that primary treatment effects CM III are dentoalveolar with minimal skeletal alterations. The findings of clinical and cephalometric evaluations confirm a significant improvement in tongue posture in Group 2 patients during comprehensive therapy by FMA. We consider the inclusion of the myofunctional appliance (FMA) essential in the multidisciplinary treatment of Class III malocclusion cases where the tongue rests on the floor of the oral cavity. The scientifically justified implementation of myofunctional orthodontic technologies requires appropriate legal regulation at the legislative level. In particular, it necessitates the formal incorporation of relevant provisions into clinical protocols, healthcare service standards, and accreditation requirements for medical professionals. The findings of this study demonstrate not only the clinical effectiveness of the applied technologies but also the urgent need for a legal framework to support an integrated interdisciplinary approach to the treatment of malocclusions. Conclusions: A tongue positioned low in the mouth during critical growth periods contributes to the stimulation of mandibular development, in line with M. Moss’s functional matrix theory of bone growth. For orthodontists, establishing a regular adaptive swallowing pattern is crucial, as it enhances treatment outcomes, reduces treatment time, and helps prevent relapse. Our findings highlight the effectiveness of labiotherapy developed by Patrick Fellus, as a regular swallowing pattern was achieved in the majority of patients (85.7%) after just four months of therapy. Legislative recognition of these technologies will facilitate the integration and harmonization of dental, functional, and general medical practices, thereby promoting a more cohesive and interdisciplinary approach to healthcare delivery.